2013
DOI: 10.1186/1472-6947-13-23
|View full text |Cite
|
Sign up to set email alerts
|

Why mobile health app overload drives us crazy, and how to restore the sanity

Abstract: BackgroundSmartphones and tablet computers have become an integral part of our lives. One of their key features is the possibility of installing third-party apps. These apps can be very helpful for improving health and healthcare. However, medical professionals and citizens are currently being overloaded with health apps. Consequently, they will have difficulty with finding the right app, and information and features are fragmented over too many apps, thereby limiting their usefulness.DiscussionIn order to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 16 publications
(17 reference statements)
1
85
0
6
Order By: Relevance
“…Hence, a successful adoption of the app into clinical practice is likely to require additional decision support and training to help nurses to provide blended care by choosing exercises to recommend to their clients or schedule into their client meetings [44]. This kind of tailored support could also be built into the app [45], which could ease the adoption by reducing the time and effort needed to get thoroughly familiar with the app. In a wider context, decision support tools for choosing the suitable evidence-based app for a particular client are also needed [46].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a successful adoption of the app into clinical practice is likely to require additional decision support and training to help nurses to provide blended care by choosing exercises to recommend to their clients or schedule into their client meetings [44]. This kind of tailored support could also be built into the app [45], which could ease the adoption by reducing the time and effort needed to get thoroughly familiar with the app. In a wider context, decision support tools for choosing the suitable evidence-based app for a particular client are also needed [46].…”
Section: Discussionmentioning
confidence: 99%
“…Van Velsen et al originally underlined that one of the major limitations is the growing number of available apps: this overload makes it difficult for medical professionals (and citizens) to find the tools more appropriate to a given situation. 29 Moreover, the authors consider that information and features are fragmented over too many apps, thereby limiting their usefulness. Bender et al reported in a recent review a lack of scientific data supporting the use of cancer-related apps scientifically supported data.…”
Section: Discussionmentioning
confidence: 99%
“…A cada dia surgem novos aplicativos no mercado, os números são gigantescos, um verdadeiro "app overload" 1 ( VAN VELSEN et al, 2013) que acaba por inundar e confundir seus usuários. Dentro dos milhares existentes, os aplicativos de saúde ocupam uma grande fatia deste mercado.…”
Section: Os Aplicativos De Saúdeunclassified